Managing People and Technological Change - Bailey John (Pitman Publishing, 1993)
This book explores the impact of new technology on people and their jobs and how, through the use of job design and work organizational concepts, it is possible to achieve a match between human and technological needs. People and Technology, Opportunities Created by Technological Change, Impact of Automation and Computerization, Corporate Culture and Technological Change, Results and Conclusions - Is it Possible to Introduce New Technology in a Human Way.